Balancing human expertise and ai in cybersecurity - Maksym Zaiets; Olena Hurska; Гурська Олена (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In our interconnected world, digital infrastructure is the backbone of almost everything we do. From banking and shopping to how we communicate, educate ourselves, and even govern our nations, we depend on digital systems. This growing dependence has turned cyberspace into a vital area that supports our social, economic, and political well-being. However, this reliance also creates more ways for cybercriminals to attack. Today's cyberattacks are often carried out by automated systems that use artificial intelligence (AI). This makes them quicker, more complex, and harder to spot. Basic security tools and human monitoring are no longer enough to deal with these changing threats. The relevance of this study lies in addressing this imbalance by exploring how AI can be integrated with human expertise to strengthen cybersecurity. The novelty of this research is reflected in its focus on achieving synergy between AI automation and human analytical judgment to create adaptive, intelligent, and ethical security systems. The objective of this research is to analyze the role of AI in threat detection, incident response, and predictive defense, while also evaluating its limitations, risks, and the irreplaceable role of human expertise in maintaining balance and accountability.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cybersecurity; digital infrastructure; automated threats